THE STRUCTURE AND GUIDELINES OF PRE-VOCATIONAL EDUCATION AND ASSISTANCE FOR PUPILS WITH MILD INTELLECTUAL DISABILITIES - Valaikiene, Aiste; Kaffemaniene, Irena; Baranauskiene, Ingrida (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The research aims to disclose the structure and guidelines of pre-vocational education and assistance for pupils with mild intellectual disabilities. In order to achieve the research aim, the qualitative research was chosen. It was conducted using modified elements of Delphi group discussion method. The study participants were highly qualified specialists (13 experts) with 5 to 25 years’ experience of educating pupils with special educational needs or providing educational assistance to them. The authors of the research systematized specialists’ approaches towards pre-vocational education of pupils with mild intellectual disabilities, discussed possibilities of improving early preparation of these pupils for the world of labour.